2020
DOI: 10.1186/s12974-020-01962-7
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of P2X7R in the experimental autoimmune encephalomyelitis model of multiple sclerosis using [11C]SMW139

Abstract: Background Non-invasive imaging of the activation status of microglia and the ability to identify a pro- or anti-inflammatory environment can provide valuable insights not only into pathogenesis of neuro-inflammatory and neurodegenerative diseases but also the monitoring of the efficacy of immunomodulatory therapies. P2X7R is highly expressed on pro-inflammatory microglia and [11C]SMW139, a specific P2X7R tracer for positron emission tomography imaging, showed good pharmacokinetics, stability, and brain permea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Immunohistochemical staining indicated that the levels of P2Y12 receptor were decreased in the brains derived from patients with multiple sclerosis and AD cases ( 217 ). Several P2X7 receptor tracers including [ 11 C]GSK1482160 ( 110 , 111 ), [ 11 C]JNJ-47965567 (A-740003) ( 120 ), [ 18 F]JNJ-64413739 ( 112 , 114 ), [ 11 C]JNJ-54173717 ( 113 ), [ 11 C]SMW139 ( 118 ), and [ 18 F]PTTP ( 218 ). Janssen et al showed that [ 11 C]SMW139 can detect with high affinity and specificity to the P2X7 receptor by using rAAV3flag-hP2X7R rat model overexpressing human P2X7 receptor ( 119 ).…”
Section: Neuroinflammation Positron Emission Tomography Imagingmentioning
confidence: 99%
“…Immunohistochemical staining indicated that the levels of P2Y12 receptor were decreased in the brains derived from patients with multiple sclerosis and AD cases ( 217 ). Several P2X7 receptor tracers including [ 11 C]GSK1482160 ( 110 , 111 ), [ 11 C]JNJ-47965567 (A-740003) ( 120 ), [ 18 F]JNJ-64413739 ( 112 , 114 ), [ 11 C]JNJ-54173717 ( 113 ), [ 11 C]SMW139 ( 118 ), and [ 18 F]PTTP ( 218 ). Janssen et al showed that [ 11 C]SMW139 can detect with high affinity and specificity to the P2X7 receptor by using rAAV3flag-hP2X7R rat model overexpressing human P2X7 receptor ( 119 ).…”
Section: Neuroinflammation Positron Emission Tomography Imagingmentioning
confidence: 99%
“…Imaging microglia activation and astrocytosis: There is a lack of imaging tracers for detecting the dynamic phenotypes of microglia, especially the disease-associated microglia with more specific cellular location and activation status (proinflammatory/anti-inflammatory). Several promising targets are currently under investigation such as purinergic P2X7 receptors, P2Y12 receptors ( Beaino et al, 2017 , 2020 ; Van Weehaeghe et al, 2020 ), cyclooxygenase-1 and cyclooxygenase-2 ( Ohnishi et al, 2014 , 2016 ; Shukuri et al, 2016 ), macrophage colony-stimulating factor 1 receptor ( Horti et al, 2019 ; Zhou X. et al, 2021 ), cannabinoid receptor type 2 ( Savonenko et al, 2015 ; Ni et al, 2019 , 2021a ), imidazoline-2 binding sites, and receptor for advanced glycation end products ( Cary et al, 2016 ; Luzi et al, 2020 ). Recent studies highlighted the role of astrocyte in tau pathology and the associated neurodegeneration ( Bussian et al, 2018 ; Ferrer et al, 2018 ; Richetin et al, 2020 ; Maté de Gérando et al, 2021 ; Wang C. et al, 2021 ; Wang and Ye, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several promising targets are currently under investigation such as purinergic P2X7 receptors, P2Y12 receptors (Beaino et al, 2017(Beaino et al, , 2020Van Weehaeghe et al, 2020), cyclooxygenase-1 and cyclooxygenase-2 (Ohnishi et al, 2014(Ohnishi et al, , 2016Shukuri et al, 2016), macrophage colonystimulating factor 1 receptor (Horti et al, 2019;, cannabinoid receptor type 2 (Savonenko et al, 2015;Ni et al, 2019Ni et al, , 2021a, imidazoline-2 binding sites, and receptor for advanced glycation end products (Cary et al, 2016;Luzi et al, 2020). Recent studies highlighted the role of astrocyte in tau pathology and the associated neurodegeneration (Bussian et al, 2018;Ferrer et al, 2018;Richetin et al, 2020;Maté de Gérando et al, 2021;Wang C. et al, 2021;Wang and Ye, 2021).…”
Section: Imaging Microglia Activation and Astrocytosismentioning
confidence: 99%
“…P2X 7 R was also over‐expressed in inflammatory microglia in white matter of active and chronic active MS lesions [ 25 ]. Similarly, P2X 7 R expression was increased in activated microglia in the EAE rat model during the disease phase [ 25 , 75 ]. In AD mouse models, neuroinflammation induced by Aβ peptides increased the expression of P2X 7 R on microglia in senile plaques at advanced and late pathological stages [ 76 ], and P2X 7 R expression levels in plaque associated microglia progressively rose with age in line with the development of AD pathogenesis [ 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adamantyl benzamide [ 11 C]SMW139 was used in a preclinical PET imaging study in EAE rats, displaying significantly elevated tracer uptake in spinal cord at the maximum of clinical symptoms in severe–relapsing EAE rats compared with recovery phase and control animals, but not in rats with mild–acute disease progression [ 75 ], probably due to milder inflammatory response. A first‐in‐human study showed good pharmacokinetics and quantifiable brain uptake of [ 11 C]SMW139 in a small set of healthy volunteers and MS patients [ 83 ].…”
Section: Introductionmentioning
confidence: 99%